2007
DOI: 10.1532/ijh97.06094
|View full text |Cite
|
Sign up to set email alerts
|

Primary Gastric Hodgkin's Lymphoma Expressing a B-Cell Profile Including Oct-2 and Bob-1 Proteins

Abstract: Classic Hodgkin's lymphoma (cHL) most often involves lymph nodes, and gastric involvement is rare. Hodgkin's and Reed-Sternberg (H-RS) cells in cHL are known to often lack expression of several B-lineage markers, such as CD20, CD79a, Oct-2, and Bob-1. We present an extremely rare case of mixed-cellularity cHL in the stomach in which expression of these B-cells was detected immunohistochemically. The patient was an 83-year-old Japanese woman who developed a sensation of abdominal fullness and appetite loss. End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
10
1
1
Order By: Relevance
“…However, EBV infection was not present in the pathologic portion of the stomach analyzed in our case. Regarding cases of HL located at unusual sites, such as gastric HL, some authors have suggested that the gastric marginal zone B-cell lymphoma of the mucosa-associated lymphoid tissue (MALT) type, which is similar to DLBCL, may be a precursor lesion for CHL [9]. The results of tests for H. pylori were positive in our case; however, none of our findings suggested the presence of gastric MALT lymphoma.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, EBV infection was not present in the pathologic portion of the stomach analyzed in our case. Regarding cases of HL located at unusual sites, such as gastric HL, some authors have suggested that the gastric marginal zone B-cell lymphoma of the mucosa-associated lymphoid tissue (MALT) type, which is similar to DLBCL, may be a precursor lesion for CHL [9]. The results of tests for H. pylori were positive in our case; however, none of our findings suggested the presence of gastric MALT lymphoma.…”
Section: Discussioncontrasting
confidence: 55%
“…Non-Hodgkin's B-cell lymphomas represent the vast majority of primary gastric lymphomas [1], whereas primary Hodgkin's lymphoma (HL) involving the stomach is exceedingly rare and only a few cases have been reported in the medical literature to date [2-9]. A diagnosis of HL depends primarily on the detection of Reed-Sternberg cells using light microscopy techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Hippo et al 7 discovered a high and specific expression of POU2F2 in metastatic GC tissue, but the molecular mechanisms underlying its effect in GC were far from clear. This study not only reaffirmed the increased expression of POU2F2 in metastatic GC but, more importantly, it also revealed the role of POU2F2 in conferring GC cell metastasis through a direct regulation of ROBO1 and the activation of SLIT2/ROBO1 signalling.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies have indicated that POU2F2 is normally expressed in B cells and B cell lineage tumour cells [2][3][4] to regulate Ig, B cell proliferation and B cell differentiation genes. 5 Recent studies have identified POU2F2 expression in pancreatic cancer, 6 gastric cancer (GC) 7 and other epithelial tumours.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Furthermore, Bob-1 and Oct-2, which are thought to be B-lineage markers, were both expressed in the present case. Recent studies have rarely found the expression of Bob-1 in RS cells in cHL, 27 and the absence of functional Oct-2 and/or Bob-1 in RS cells in cHL has also been reported. 28,29 In addition to immunophenotype, the characteristics of the present case, including the site of primary lesions, the absence of other lymph node lesions and the relatively old age, appear to suggest that the present case is aEBVBLPD, rather than cHL.…”
Section: Discussionmentioning
confidence: 96%